2018
DOI: 10.3390/ijerph15061289
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Intersectionality and Resiliency among Transgender Adolescents: Exploring Pathways among Peer Victimization, School Belonging, and Drug Use

Abstract: Transgender youth experience elevated levels of victimization and may therefore report greater drug use than their cisgender peers, yet little is known about protective factors like school belonging that may mediate this relationship. Further, scant research has explored the experiences of youth at the intersection of transgender identity and youth of color status or low socioeconomic status, especially with respect to these multiple minority statuses’ associations with peer victimization, drug use, and school… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
56
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(59 citation statements)
references
References 51 publications
1
56
1
1
Order By: Relevance
“…4952 Such behaviors maybe even more common in transgender women who are also racial and ethnic minorities. 53,54 In addition to the risks caused by minority stress and social stigma, there is also some suggestion that cross-sex hormone therapy may contribute to insulin resistance and weight gain in a subset of transgender women. 55…”
Section: Discussionmentioning
confidence: 99%
“…4952 Such behaviors maybe even more common in transgender women who are also racial and ethnic minorities. 53,54 In addition to the risks caused by minority stress and social stigma, there is also some suggestion that cross-sex hormone therapy may contribute to insulin resistance and weight gain in a subset of transgender women. 55…”
Section: Discussionmentioning
confidence: 99%
“…Other factors, including support from friends, LGBQ connectedness, and having a steady partner, were also found to be protective factors against poor mental health (Shilo et al, 2015). Additionally, other work has found that transgender youth were more likely to have positive mental health outcomes when they perceived that they received social support from family and friends (Hatchel & Marx, 2018).…”
Section: Discussionmentioning
confidence: 89%
“…Research has demonstrated that health risks among youth who identify as lesbian, gay or bisexual are mediated by in-school peer victimization (Bontempo & D'Augelli, 2002). Creating supportive school environments through targeted policy and program development could help to mitigate these health risks (Blake et al, 2001;Hatchel & Marx, 2018;Hatzenbuehler et al, 2014), particularly since schools are well-positioned to address inequities (Gower et al, 2018). In addition, promoting inclusivity and visibility of LGBTQ youth while implementing comprehensive, evidence-based sexual and reproductive health curricula and programs might help to improve knowledge of pregnancy prevention methods, as well as knowledge of available, adolescent-and LGBTQ-friendly clinical services (Boyce et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Por último, señalar que aunque es necesario incrementar el conocimiento sobre las características de contexto en el acoso escolar (Skues et al,2005), la investigación más reciente coincide en identificar el efecto mediador del sentido de pertenencia escolar en la relación entre la victimización por acoso escolar y el ajuste psicológico (Hatchel & Marx, 2018;Hatchel, Merrin, & Espelage, 2019), o los efectos que la pertenencia puede tener sobre la victimización (Jiménez, Musitu, Ramos, & Murgui, 2009). A pesar de que nuestro diseño no permite establecer en qué medida la baja pertenencia de los alumnos se deben a la experiencia de victimización, o si el bajo sentido de pertenencia favorece la victimización por acoso escolar, la relación que confirma el modelo resulta de gran interés para el diseño de los programas de prevención e intervención en acoso escolar (Novo, Fariña, Seijo, Vázquez, & Arce, 2019;Rose, Simpson, & Ellis, 2016;Wormington, Anderson, Schneider, Tomlinson, & Brown, 2016).…”
Section: Discussionunclassified